Implementation and management of a circular public procurement contract for furniture - Lingegård, Sofia; von Oelreich, Kristina (Frontiers in Sustainability, 2023)
Circular public procurement (CPP) is one way to increase sustainability and circularity in public spending. As previous research focuses primarily on procurement, more insight is needed into the latter stages CPP. Real-life examples of CPP implementation are also required to promote the concept to practitioners, improve governance, and add depth to the literature. This study, therefore, provides in-depth knowledge of CPP implementation and management by analyzing a case of circular furniture flows and its implications for the procuring organization. The focus on furniture is motivated by the large volumes sent to landfills every year despite its remanufacturing potential, as well as the large environmental impact for production, a potentially long lifetime, and an often-high purchasing price. The results show that strategic decisions to prioritize sustainability are necessary when resource efficiency and cost reductions do not align in a short-term perspective. A more centralized governance structure facilitates decisions on reuse, remanufacturing and disposal in an organization, e.g., coordination of products for remanufacturing, pooling products for reuse, and standardization of design choices. Follow-up and inventory systems are crucial tools for integrating previously installed products with CPP, keeping track of circular flows, and providing feedback to improve subsequent procurements. Crucial elements in the follow-up include adaptation to circularity in the economic system and accounting for the prolonged life and reuse of furniture. The study's results emphasize how an organization's prerequisites play an essential part in the implementation of CPP and that contextual solutions are needed for circular challenges. The study contributes to the fields of policy implementation, CPP, and the use of circular business models in a public context, as well as to the less explored field of procurement in a circular economy context. Suggestions for future research include studies on product categories with other environmental impact profiles and on waste management regulations that can make or break circular systems.